Transdifferentiation of pancreatic progenitor cells to hepatocyte-like cells is not serum-dependent when facilitated by extracellular matrix proteins - Gratte, F.; Pasic, S.; Olynyk, John; Yeoh, G.; Tosh, D.; Coombe, Deidre; Tirnitz-Parker, Nina (Nature Publishing Group, 2018)
The rising prevalence of chronic liver disease, coupled with a permanent shortage of organs for liver transplantation, has sparked enormous interest in alternative treatment strategies. Previous protocols to generate hepatocyte-like cells (HLCs) via pancreas-to-liver transdifferentiation have utilised fetal bovine serum, introducing unknown variables and severely limiting study reproducibility. Therefore, the main goal of this study was to develop a protocol for transdifferentiation of pancreatic progenitor cells to HLCs in a chemically defined, serum-free culture medium. The clonal pancreatic progenitor cell line AR42J-B13 was cultured in basal growth medium on uncoated plastic culture dishes in the absence or presence of Dexamethasone on uncoated, laminin-or fibronectin-coated culture substrata, with or without serum supplementation. The hepatocytic differentiation potential was evaluated: (i) morphologically through bright-field and scanning electron microscopy, (ii) by assessing pancreatic and hepatic marker expression and (iii) by determining the function of HLCs through their ability to synthesise glycogen or take up and release indocyanine green. Here we demonstrate for the first time that transdifferentiation of pancreatic cells to HLCs is not dependent on serum. These results will assist in converting current differentiation protocols into procedures that are compliant with clinical use in future cell-based therapies to treat liver-related metabolic disorders.